Fate of A Person in Shukur Kholmirzayev’s Story Which is Called “Bitiktosh” (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article analyzes the story "Bitiktosh" by the talented writer Shukur Kholmirzayev. The story is about the absurdity of Soviet ideology and its atheistic propaganda, and how dangerous it is for people's destinies, exemplified through the fate of Boyquvar